Pembelajaran Secara dalam Talian: Tahap Kesediaan dan Keberkesanan Pelaksanaannya kepada Pelajar: Online Teaching: Level of Readiness and The Effectiveness of Its Implementation to Students (LSP International Journal, 2022)
The aim of this study is to explain the preparation level and the effectiveness of online learning to students. The data were obtained through library research and observation including questionnaires form as the instrument. 32 form two students from Sekolah Menengah Kebangsaan Kuala Jengal, Dungun, Terengganu were selected as respondents. Findings show that the level of students' readiness for online learning methods is at a satisfactory level. The effectiveness of online learning methods for the subjects of the Malay language among students was analyzed using the constructivist learning theory. The results showed that students preparation level in joining online learning are higher and almost all of them had facilities to join the classes. The study also shows that online learning have a positive effect on students ’interest and motivation. However, student involvement in learning activities is at a satisfactory level because not all students are actively involved in the activities provided by the teacher. In terms of implications, this study help to increase knowledge on issues related to online learning, and help students and teachers to adapt to new teaching methods to ensure that educational needs can be met.